Annual Plan 1999-2000 Proposals Volume I Haryana State - Planning Commission (Planning Commission, 1999)
An outlay of Rs.2300.00 crore has been approved for Annual Plan, 1999-2000 against the revised outlay of Rs.1800 crore of Annual Plan 1998-99. While making sectoral distribution of this outlay, highest Priority has been accorded to the creation of infrastructure of power, irrigation and roads. Irrigation sector has been allocated an outlay of Rs.581.00 crore which constitutes 25.3% of the plan. This includes an amount of Rs.355.00 crore for World Bank Aided Water Resources Consolidation Project.
Planning Department, Government of Haryana